Detection of Papua New Guinea Thalassemia Alpha Mutation in Gayo, Sumba, Ternate, and Timika Populations - Nurfitriani, Risya; Abinawanto, Abinawanto; Noviyanti, Rintis; Trianti, Lely; Nainggolan, Ita M. (UI Scholars Hub, 2014)
Papua New Guinea (PNG) mutation is a point mutation that occurs in noncoding region of alpha globin clusters. Polymorphism promotes an additional recognition site for transcription factor (GATA-1) which presumably downregulates alpha globin synthesis. The aim of this research is to detect PNG mutation in other populations in Indonesia, thus the results will be used for completing standard diagnoses in detecting alpha thalassemia mutation based on ethnic background. The method used in detecting PNG mutation was PCR-RFLP. Detection of 399 samples (MCH